Anoikis resistance––protagonists of breast cancer cells survive and metastasize after ECM detachment - Dai, Yalan; Zhang, Xinyi; Ou, Yingjun; Zou, Linglin; Zhang, Duoli; Yang, Qingfan; Qin, Yi; Du, Xiuju; Li, Wei; Yuan, Zhanpeng; Xiao, Zhangang; Wen, Qinglian (Cell communication and signaling, 2023)
Breast cancer exhibits the highest global incidence among all tumor types. Regardless of the type of breast cancer, metastasis is a crucial cause of poor prognosis. Anoikis, a form of apoptosis initiated by cell detachment from the native environment, is an outside-in process commencing with the disruption of cytosolic connectors such as integrin-ECM and cadherin-cell. This disruption subsequently leads to intracellular cytoskeletal and signaling pathway alterations, ultimately activating caspases and initiating programmed cell death. Development of an anoikis-resistant phenotype is a critical initial step in tumor metastasis. Breast cancer employs a series of stromal alterations to suppress anoikis in cancer cells. Comprehensive investigation of anoikis resistance mechanisms can inform strategies for preventing and regressing metastatic breast cancer. The present review first outlines the physiological mechanisms of anoikis, elucidating the alterations in signaling pathways, cytoskeleton, and protein targets that transpire from the outside in upon adhesion loss in normal breast cells. The specific anoikis resistance mechanisms induced by pathological changes in various spatial structures during breast cancer development are also discussed. Additionally, the genetic loci of targets altered in the development of anoikis resistance in breast cancer, are summarized. Finally, the micro-RNAs and targeted drugs reported in the literature concerning anoikis are compiled, with keratocin being the most functionally comprehensive.